Group A Streptococcus-Induced Activation of Human Plasminogen Is Required for Keratinocyte Wound Retraction and Rapid Clot Dissolution - Vu, Henry M.; Hammers, Daniel E.; Liang, Zhong; Nguyen, Gabrielle L.; Benz, Mary E.; Moran, Thomas E.; Higashi, Dustin L.; Park, Claudia J.; Ayinuola, Yetunde A.; Donahue, Deborah L.; Flores-Mireles, Ana L.; Ploplis, Victoria A.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Invasive outcomes of Group A Streptococcus (GAS) infections that involve damage to skin and other tissues are initiated when these bacteria colonize and disseminate via an open wound to gain access to blood and deeper tissues. Two critical GAS virulence factors, Plasminogen-Associated M-Protein (PAM) and streptokinase (SK), work in concert to bind and activate host human plasminogen (hPg) in order to create a localized proteolytic environment that alters wound-site architecture. Using a wound scratch assay with immortalized epithelial cells, real-time live imaging (RTLI) was used to examine dynamic effects of hPg activation by a PAM-containing skin-trophic GAS isolate (AP53R+S−) during the course of infection. RTLI of these wound models revealed that retraction of the epithelial wound required both GAS and hPg. Isogenic AP53R+S− mutants lacking SK or PAM highly attenuated the time course of retraction of the keratinocyte wound. We also found that relocalization of integrin β1 from the membrane to the cytoplasm occurred during the wound retraction event. We devised a combined in situ-based cellular model of fibrin clot-in epithelial wound to visualize the progress of GAS pathogenesis by RTLI. Our findings showed GAS AP53R+S− hierarchically dissolved the fibrin clot prior to the retraction of keratinocyte monolayers at the leading edge of the wound. Overall, our studies reveal that localized activation of hPg by AP53R+S−via SK and PAM during infection plays a critical role in dissemination of bacteria at the wound site through both rapid dissolution of the fibrin clot and retraction of the keratinocyte wound layer.